Young people with congenital heart disease — Transitioning to adult care. (March 2018) - Uzark, Karen; Wray, Jo
Abstract: Congenital heart disease is the most common congenital anomaly and approximately 90% of those born with congenital heart disease today are likely to survive to adulthood. The majority require life-long specialist follow-up, requiring transition to adult-oriented services. The high frequency of patients lost to follow-up and with lapses in care is daunting and suggests that current transition preparation may be inadequate. In this review we define transition and the goals of transition and describe the concept of transition readiness. We identify barriers to effective transition, the key elements of preparation, and the importance of evaluating transition. Highlights: Young adults with congenital heart disease may lack knowledge and skills related to the adult lifestyle implications. Most require life-long follow-up, transitioning from family-centered pediatric care to a patient-centered adult service. Loss to follow-up and lapses of care remain concerning, with potentially serious consequences. Evaluation of transition needs, potential transition barriers and key elements of transition preparation are described.